Canine Leishmaniosis Control through the Promotion of Preventive Measures Appropriately Adopted by Citizens. (27th June 2020) - Simonato, Giulia; Marchiori, Erica; Marcer, Federica; Ravagnan, Silvia; Danesi, Patrizia; Montarsi, Fabrizio; Bononi, Carlo; Capelli, Gioia; Pietrobelli, Mario; Cassini, Rudi
Abstract : Canine leishmaniosis (CanL) is a disease caused by the protist Leishmania infantum and transmitted to dogs by sand fly (Diptera: Phlebotominae) bites. In 2005, a new autochthonous focus of CanL was recognised in the southern part of Euganei hills (northeastern Italy). In subsequent years, this outbreak was monitored, testing dogs and evaluating sand fly population. Moreover, dog owners were sensitized on the adoption of preventive measures, thanks to the collaboration of local administration, health authorities, and private veterinarians. This study includes serological tests on dogs, questionnaires submitted to dog owners regarding the use of preventive measures on their animals, and the evaluation of sand fly abundance. Data collected were statistically compared with those of previous years. The canine seroprevalence was significantly lower than that recorded at the beginning of the outbreak, despite the fact that sand fly abundance did not significantly decrease. In addition, most of the dog owners declared using regularly the topical insecticides on their dogs during the sand fly season. This experience demonstrated that a collaborative approach among scientific researchers, local authorities, and private veterinarians can achieve excellent results in the management of a leishmaniosis outbreak.